2017
DOI: 10.1016/j.neuron.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent and Differential Regulation of Local and Long-Range Excitatory Neocortical Circuits by Postsynaptic Mef2c

Abstract: Development of proper cortical circuits requires an interaction of sensory experience and genetic programs. Little is known of how experience and specific transcription factors interact to determine the development of specific neocortical circuits. Here we demonstrate that the activity-dependent transcription factor, Myocyte enhancer factor-2C (Mef2c), differentially regulates development of local vs. long-range excitatory synaptic inputs onto layer 2/3 neurons in the somatosensory neocortex in vivo. Postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…Since many of the MEF2C-regulated genes expressed in CNS neurons respond to neuronal activation with downregulation of excitatory synaptic strength (Flavell et al, 2006;Rajkovich et al, 2017), we also examined MEF2C target gene expression in response to SD or RS. We found that the downregulated DEGs shared by SD and RS were enriched for neuronal genes downregulated by Mef2c loss of function as previously 15 observed in a conditional knockout of neuronal Mef2c, Mef2c (Harrington et al, 2016).…”
mentioning
confidence: 99%
“…Since many of the MEF2C-regulated genes expressed in CNS neurons respond to neuronal activation with downregulation of excitatory synaptic strength (Flavell et al, 2006;Rajkovich et al, 2017), we also examined MEF2C target gene expression in response to SD or RS. We found that the downregulated DEGs shared by SD and RS were enriched for neuronal genes downregulated by Mef2c loss of function as previously 15 observed in a conditional knockout of neuronal Mef2c, Mef2c (Harrington et al, 2016).…”
mentioning
confidence: 99%
“…Changes in excitatory (E) and/or inhibitory (I) synaptic transmission are associated with numerous neuropsychiatric disorders, including ASD (Antoine et al, 2019; Garber, 2007; Zoghbi and Bear, 2012). Conditional knockout of Mef2c alters somatosensory cortex (SSCtx) pyramidal neuron E/I synaptic transmission (Harrington et al, 2016; Rajkovich et al, 2017). In the global Mef2c -Hets (p35-p40), gross structural organization of barrel fields within cortical layer 4 of the SSCtx appeared normal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3B) or effects on presynaptic functions of local inputs (Fig. 3C,D), and might represent a compensatory effect of long-range connections (Rajkovich et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within prenatal development MEF2C has the potential to be a transcriptional regulator of a number of autism-associated genes -MEF2C binding motifs are enriched in upstream regions of genes within prenatal gene co-expression modules that harbor a number of autism-associated genes 4 . Congruent with the idea that MEF2C is important for many prenatal neurodevelopmental processes, other work has shown it is involved in neurogenesis, cell differentiation, maturation, and migration [61][62][63] as well as having later roles to play in experiencedependent synaptic development and cell death 52,53,64,65 . MEF2C is also a known downstream target of the androgen receptor (AR), thus making it highly susceptible to androgen-dependent transcriptional influence 43 .…”
Section: Discussionmentioning
confidence: 99%